The Center for Education and Art (CEA) and Fanny Abramovich's contribution to Art Education – an interview with Rosa Iavelberg (Revista de Ensino em Artes, Moda e Design, 2026)
This interview was conducted in the context of my doctoral research on Gianni Rodari's work, *Gramática da Fantasia*. During my investigation of the book's publishing history in Brazil, I identified the work of Fanny Abramovich, the organizer of the collection in which the book was published, which went beyond the publishing field. Abramovich also stood out in the field of art education in São Paulo, a dimension of her career that I was previously unaware of. Her work demonstrated the promotion of innovative pedagogical practices, showing how art and education could complement each other. In the course of the research, especially during the qualifying exam, I learned that the art educator Rosa Iavelberg had been a student in the teacher training course at the São Paulo Center for Education and Art, an institution affectionately called "Fanny's Little School." This discovery sparked my interest in understanding more deeply how this space functioned, which offered art courses for children, as well as art training programs for teachers. The center was an important laboratory for artistic experimentation in the 1960s and 1970s, promoting innovative methodologies and reflections on teaching practice.Motivated by this context, I requested an interview with Rosa Iavelberg with the aim of recording her memories and perceptions of her experience as a student at Fanny's Little School. The conversation sought to document aspects of the center's operation, the activities and courses developed, as well as Fanny Abramovich's contribution to the field of arts and education in São Paulo during that period.
Keywords: Fanny Abramovich; art; education; arts education